Enhancement in xylonate production from hemicellulose pre-hydrolysate by powdered activated carbon treatment. (November 2020) - Dai, Lin; Jiang, Wenfei; Zhou, Xin; Xu, Yong
Highlights: PAC treatment decreases inhibitors and viscosity of concentrated pre-hydrolysate. PAC treatment enables the air-aerated and agitated fermentation of XA. 143.6 g/L XA with a volumetric productivity of 4.48 g/L/h was achieved. Abstract: Xylonic acid can be produced with high-yield from hemicelullosic xylose, which accounts for 25% of the total sugars in lignocellulosic material. The key barrier associated with efficient bio-oxidation of hemicellulosic xylose to xylonic acid is the serious foam formed in downstream air-aerated and agitated bioreaction process, which caused by the high viscosity of concentrated pre-hydrolysate. Powdered activated carbon treatment can selectively absorb the non-sugar compounds with relatively low losses of xylose, which is beneficial for the valuable xylose derivatives production. In this present study, powdered activated carbon was employed for treating the concentrated pre-hydrolysate from diluted acid pretreated corncob. The results indicated that the powdered activated carbon treatment significantly reduced the viscosity of concentrated pre-hydrolysate and the other non-sugar compounds, which enabled scale-up lignocellulosic xylonic acid production using the air-aerated and agitated bioreactor.